Evaluation of corneas in patients with Bell's palsy using optical coherence tomography - Kaya, Mehmet Kaan; Arslan, Sermal; Kobat, Sabiha; Gül, Fatih Cem; Susaman, Nihat (Ondokuz Mayis Universitesi, 2023)
Measurements of Central Corneal Thickness and Central Corneal Epithelial Thickness Using Anterior Segment Optical Coherence Tomography (OCT) to Identify Potential Changes in Patients with Facial Paralysis. Thirty patients diagnosed with unilateral idiopathic Facial Faralysis between 2020 and 2021 at the Ear, Nose, and Throat Clinic of Elazığ City Hospital were included in our study. There were eighteen male patients (60%) and twelve female patients (40%). The mean age of the patients was 38.03±7.05 years. Central corneal thickness and central corneal epithelial thickness measurements were performed on the affected and unaffected eyes of the patients using an optical coherence tomography device at the time of diagnosis and one month later. There was no statistically significant difference in central corneal thickness and central corneal epithelial thickness between the affected and control groups in measurements taken at the time of diagnosis and one month later (p>0.05). This study represents the first evaluation of corneal tissue, a highly potentially affected structure in Facial Paralysis, using optical coherence tomography in the literature. © 2023 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: central corneal epithelial thickness; central corneal thickness; facial paralysis; optical coherence tomography